2021
DOI: 10.1098/rspb.2021.1969
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and radiation of distemper viruses in terrestrial and marine mammals

Abstract: Canine distemper virus (CDV) and phocine distemper virus (PDV) are major pathogens to terrestrial and marine mammals. Yet little is known about the timing and geographical origin of distemper viruses and to what extent it was influenced by environmental change and human activities. To address this, we (i) performed the first comprehensive time-calibrated phylogenetic analysis of the two distemper viruses, (ii) mapped distemper antibody and virus detection data from marine mammals collected between 1972 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…[ 48 ]]. However, a recent comprehensive time-calibrated phylogenetic analysis of CDV and PDV found that the two viruses diverged in the early seventeenth century with a most recent common ancestor dating to 1614 [ 68 ], putting into question the proposed evolution of CDV from MeV in the early 1700's as described above. There is now conclusive evidence of PDV also existing in the North Pacific and Western Arctic regions as well, and serologic evidence is accumulating for the existence of PDV in southern oceans [reviewed in Refs.…”
Section: Morbillivirusmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 48 ]]. However, a recent comprehensive time-calibrated phylogenetic analysis of CDV and PDV found that the two viruses diverged in the early seventeenth century with a most recent common ancestor dating to 1614 [ 68 ], putting into question the proposed evolution of CDV from MeV in the early 1700's as described above. There is now conclusive evidence of PDV also existing in the North Pacific and Western Arctic regions as well, and serologic evidence is accumulating for the existence of PDV in southern oceans [reviewed in Refs.…”
Section: Morbillivirusmentioning
confidence: 99%
“…There is now conclusive evidence of PDV also existing in the North Pacific and Western Arctic regions as well, and serologic evidence is accumulating for the existence of PDV in southern oceans [reviewed in Refs. [ 48 , 67 ]], and the spread of PDV from the North Atlantic to these other oceans appears to have occurred in the late twentieth and early twenty-first centuries [ 68 ]. Signs of disease include fever, eye and nose discharge, diarrhea, cough, weight loss, abortion, and neurological signs such as lethargy, head tremors, convulsions, and seizures [reviewed in Refs.…”
Section: Morbillivirusmentioning
confidence: 99%
“…A cinomose é uma doença altamente contagiosa, que, apesar de ocorrer principalmente em cães, pode acometer outras espécies, como felinos e canídeos silvestres, sejam terrestres ou marinhos (Stokholm et al, 2021). A doença pode acontecer em animais de todas as idades, sendo mais frequentes em filhotes entre 2 e 3 meses de idade e adultos não vacinados (Azevedo, 2013).…”
Section: Introductionunclassified
“…Having fully healthy ecosystems is unfeasible. Zoonotic diseases are becoming increasingly common and more widespread in time and space due to the destruction and fragmentation of natural ecosystems caused by anthropogenic activities and climate change (Daszak et al 2001;Stokholm et al 2021). Understanding and identifying diseases that induce high wildlife mortality and morbidity is key for ecosystem management and conservation (Loots et al 2017).…”
Section: Introductionmentioning
confidence: 99%